2012
DOI: 10.1177/1362361312458186
|View full text |Cite
|
Sign up to set email alerts
|

A randomised group comparison controlled trial of ‘preschoolers with autism’: A parent education and skills training intervention for young children with autistic disorder

Abstract: Parent education and behaviour management resulted in significant improvement in adaptive behaviour and autism symptoms at 6 months follow-up for children with greater delays in adaptive behaviour. Parent education and behaviour management was superior to parent education and counselling. We conclude that a 20-week parent education programme including skills training for parents of young children with autistic disorder provides significant improvements in child adaptive behaviour and symptoms of autism for low… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
82
0
18

Year Published

2015
2015
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 90 publications
(100 citation statements)
references
References 42 publications
0
82
0
18
Order By: Relevance
“…In comparison, research on psychoeducation in ASD is limited. To date, a few pilot studies have examined psychoeducation as a stand-alone intervention for ASD (Daley et al, 2013; Farmer & Reupert, 2013; Smith, Greenberg, & Mailick, 2012) or as a ‘control’ condition (Bearss et al, in preparation; Hardan et al, 2014; Tonge et al, 2006; 2014). …”
Section: Parent Training – Characterizing the Labelmentioning
confidence: 99%
See 1 more Smart Citation
“…In comparison, research on psychoeducation in ASD is limited. To date, a few pilot studies have examined psychoeducation as a stand-alone intervention for ASD (Daley et al, 2013; Farmer & Reupert, 2013; Smith, Greenberg, & Mailick, 2012) or as a ‘control’ condition (Bearss et al, in preparation; Hardan et al, 2014; Tonge et al, 2006; 2014). …”
Section: Parent Training – Characterizing the Labelmentioning
confidence: 99%
“…In addition, study samples were often inadequately characterized making generalization difficult. More recently, a handful of open prospective case series (Bearss et al, 2013a; Brookman-Frazee, Drahota & Stadnick, 2012; RUPP, 2007; Wacker et al, 2013) and quasi-experimental trials (Tonge et al, 2014) using a structured manual have been published. Two randomized clinical trials (RCTs) (Sofronoff, Leslie, & Brown, 2004; Whittingham, Sofronoff, Sheffield, & Sanders, 2009) have been published to date.…”
Section: Parent Training – Characterizing the Labelmentioning
confidence: 99%
“…The limited available evidence on parent training suggests that favorable response to treatment is moderated by baseline participant characteristics including object interest and more limited pretreatment communication skills (Siller, Swanson et al, 2014;Tonge et al, 2014). Other studies focused on predictors of outcome, such as the child's joint attention, involvement, enjoyment (Casenhiser et al, 2013), and age (Rogers et al, 2012); parent's intervention fidelity (Rogers et al, 2012) and quality of engagement (Kasari et al, 2010); and treatment ''dose'' (Rogers et al, 2012).…”
Section: Focused Interventionsmentioning
confidence: 99%
“…Early interventions that provide parenting strategies through psychoeducational programs have significantly decreased parental stress in these families (Feinberg et al, 2014; Tonge et al, 2006). Although effects of psychoeducational approaches on child outcomes are rarely tested, a recent study found that a parent education and counseling program that included behavior management strategies helped to improve child adaptive behaviors (Tonge, Brereton, Kiomall, Mackinnon, & Rinehart, 2014). Thus, the combination of counseling and education for ASD-specific parenting strategies may be effective for improving both parent and child outcomes.…”
mentioning
confidence: 99%